Banff Lung Report: Current knowledge and future research perspectives for diagnosis and treatment of pulmonary antibody‐mediated rejection (AMR). Issue 1 (1st August 2018) - Roux, A.; Levine, D. J.; Zeevi, A.; Hachem, R.; Halloran, K.; Halloran, P. F.; Gibault, L.; Taupin, J. L.; Neil, D. A. H.; Loupy, A.; Adam, B.A.; Mengel, M.; et al.
Abstract : The Lung session of the 2017 14th Banff Foundation for Allograft Pathology Conference, Barcelona focused on the multiple aspects of antibody‐mediated rejection (AMR) in lung transplantation. Multidimensional approaches for AMR diagnosis, including classification, histological and immunohistochemical analysis, and donor‐ specific antibody (DSA) characterization with their current strengths and limitations were reviewed in view of recent research. The group also discussed the role of tissue gene expression analysis in the context of unmet needs in lung transplantation. The current best practice for monitoring of AMR and the therapeutic approach are summarized and highlighted in this report. The working group reached consensus of the major gaps in current knowledge and focused on the unanswered questions regarding pulmonary AMR. An important outcome of the meeting was agreement on the need for future collaborative research projects to address these gaps in the field of lung transplantation. Abstract : This article reports the Banff 2017 session dedicated to antibody‐mediated rejection in lung transplantation.